Atendimento em grupo na fonoaudiologia: feitos e (d)efeitos - Araújo, Manuela Luchesi Brazil (2010)
Objective: to search the theory of the clinical process resulting from the analysis of the therapeutical effects of the group words about the symptoms of the speech of their own group, guided by a Speech and language clinics, based on the notion of the structure that has as object the working of the language symptoms. Justification: the recognition of that the different practical and theories of attendance in group in the area of Speech and language clinics,, with adoption of concepts of other areas without joint, reflection or (re)structing with the phonoaudiological pratical clinic, don´t allow the reach of a structure that legitimizes the relation between practical of attendance in group and the phonoaudiological clinic. Hypothesis: the functioning of the group is articulated to a practical clinic supported for the notion of structure and guided by a model of functioning of the language symptoms; the recognition that the group is made for the functioning; the affirmation that the goal procedure of the sanction reached for the Speech and language therary and the speech sanction operated by the citizens of the group potentiate the effects that operate the intersubjective displacements. Theoretical and methodological aspects: adoption of the model of functioning of the symptoms of language for the analysis of the pieces of speech and language therary sessions of the attendance in group of two groups of children with symptoms in the language, cared for fuor month, performed in a UBS of the capital of São Paulo. Conclusions: the functioning of the Speech and language therary attendance in group is marked by the Speech and language therary intervention of the handling of the sanction and increased by the sanctions operated for the citizens of the group among them, that produce effects on the symptoms of speaks of the group